Regulation of microglial transcription factor MEF2C by Alzheimer's disease‐relevant stimuli. (December 2021) - Hassan, Ahmed; Scott, Hannah; Hill, Matt
Abstract: Background: The transcription factor, myocyte enhancer factor‐2C (MEF2C), is a master regulator of gene expression in microglia, the brain‐resident immune cells. In recent years, microglia have become increasingly recognized as key players in Alzheimer's disease (AD)‐ they are thought to be protective in early AD and detrimental in late AD by producing pro‐inflammatory cytokines that contribute to brain inflammation. Both AD and aging have been associated with increased microglial inflammatory responses and chronic inflammation. MEF2C was recently identified as an 'off‐factor' helping to restrain the microglial inflammatory response and may therefore be a potential target for AD treatment. This research project aimed to understand the regulation of microglial MEF2C by AD‐relevant inflammatory stimuli lipopolysaccharide (LPS) and polyinosinic:polycytidylic (polyI:C). Method: Mouse microglial cell line, BV2, was exposed to LPS or PolyI:C for 3 h and 24 h. Levels of MEF2C protein and RNA were measured by western blot and qPCR, respectively. Furthermore, MEF2C activity in response to the inflammatory stimuli was investigated by measuring the cytoplasmic and nuclear localisation of MEF2C inhibitor histone deacetylase 4 (HDAC4) and by analysing the expression of two predicted target genes of MEF2C, Ccl3 and Mndal, by qPCR. Result: Expression of whole‐cell microglial MEF2C was reduced in BV2 cells exposed to LPS and PolyI:C for 3hrs but was increased at 24hrs LPS exposure relative to the control. Cytoplasmic HDAC4 expression was reduced with LPS exposure, which was more pronounced at the 24‐hour BV2 cells exposure. In addition, the inflammatory stimuli increased the amount of a potential amino‐terminal HDAC4 fragment in the nucleus. Furthermore, Ccl3 and Mndal expression in response to LPS and PolyI:C at 3 hours was reduced. Conclusion: This research project provided evidence that AD‐relevant inflammatory stimuli downregulate microglial MEF2C expression. In addition, MEF2C transcriptional activity was reduced by these inflammatory stimuli, possibly via induction of caspase‐3, leading to fragmentation of HDAC4 and subsequent translocation of HDAC4 amino‐terminal fragment into the nucleus at MEF2C‐targeted promoters. Overall, this provided a mechanistic insight on how the crucial function of MEF2C is lost during inflammatory conditions.